PENGARUH KEAKTIFAN PESERTA DIDIK DALAM ORGANISASI DAN MOTIVASI BELAJAR TERHADAP PRESTASI BELAJAR PESERTA DIDIK DI SEKOLAH MENENGAH ATAS NEGERI 7 KOTA TANGERANG TAHUN PELAJARAN 2018/2019 - Sri Maulidia; Femi Handayani (Journal of Business Education and Social, 2020)
This research aims to determine how much influence the activeness of students in the organization and learning motivation on student achievement in SMA Negeri 7 kota Tangerang. This research is a research using a quantitative method approach. The population in this research were students in SMA Negeri 7 kota Tangerang who participated in the organization's activities. The samples taken were 131 students with a sampling technique that is saturated samples using the Solvin formula. The data collection techniques using a questionnaire (questionnaire) and interviews. The instrument in this study was in the form of a Likert scale. Data analysis uses multiple regression. From the results of the study it can be concluded as follows: (1) the activeness of students in organizations does not affect learning achievement as indicated by the significance value of 0.510 more than 0.05. (2) students' learning motivation has no effect on learning achievement, this is indicated by a significance value of 0.556 over 0.05. R2 value of 0.125 means that 1.25% of student achievement is influenced by student activity in the organization and learning motivation. While 98.75% is explained by other factors not examined in this study.Keywords: student activeness in the organization, learning motivation, learning achievement